Traces of guilt - Henderson, Dee (Henderson, Dee. Evie Blackwell cold case., 2016)
Gabriel Thane is the sheriff and lifetime resident of Carin County Illinois, committed to upholding the law and keeping the residents safe. Lieutenant Evie Blackwell is a State Police Detective skilled at investigations. She launches a new task force to reexamine unsolved crimes across the state. She begins work with the sheriff's department on a few of its most troubling missing-persons cases, a deputy, his wife and eleven-year old son's disappearance, and in an unrelated case involving a six-year-old girl abducted from a hotel. As she examines old evidence, she finds a connection to a third cold case.